Material Story in Narrative Architecture: Capturing Dialogue Between Material and Nature - Suryantini, Rini; Putri, Irfany Roihana; Atmodiwirjo, Paramita (Department of Architecture Universitas Muhammadiyah Jakarta, 2025)
This paper discusses how material story constructs narrative architecture by emphasizing the dynamic dialogue between material and its surroundings. It argues that a story embedded within a material can hold greater importance than its physical form, providing a basis for developing narrative architecture. When material is viewed as something alive, its journey becomes important to study. The story acts as a vehicle to reveal the nature of a material, including the hidden one, allowing other agencies to be part of the story. Focusing on brick materiality as a case study, this paper examines how material responses emerge through interactions between the brick and nature. Based on the grouping of the responses, four material-nature dialogues can be categorized: patterning, reflecting, growing, and nesting. This analysis demonstrates that material story allows materiality to be interpreted narratively, generating multiple stories as a basis for scenarios within narrative architecture, enriching the architectural design process.